2017
DOI: 10.3732/apps.1700005
|View full text |Cite
|
Sign up to set email alerts
|

Development of microsatellite loci in Mediterranean sarsaparilla (Smilax aspera; Smilacaceae) using transcriptome data

Abstract: Premise of the study:Although several microsatellite markers of Smilax aspera (Smilacaceae) have been reported in a previous study, due to universality issues in cross-population amplification, we have newly developed microsatellite markers for S. aspera based on transcriptome data to further investigate gene flow and genetic structure of its circum-Mediterranean, East African, and South Asian populations.Methods and Results:A total of 4854 simple sequence repeat (SSR) primer pairs were designed from 99,193 co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 12 publications
0
7
0
Order By: Relevance
“…We developed 126 and 452 intergeneric and intrageneric polySSR markers between Oresitrophe and Mukdenia and within Oresitrophe . Twelve pairs of candidate gSSR primers were selected to test their transferability following Qi et al [ 94 ], primer transferability was detected using 2% agarose gels, and amplification was considered successful when one clear distinct band was visible in the expected size range. In total, 100% of the developed microsatellite markers we selected could be successfully amplified in two populations of M. rossii and four populations of O. rupifraga .…”
Section: Discussionmentioning
confidence: 99%
“…We developed 126 and 452 intergeneric and intrageneric polySSR markers between Oresitrophe and Mukdenia and within Oresitrophe . Twelve pairs of candidate gSSR primers were selected to test their transferability following Qi et al [ 94 ], primer transferability was detected using 2% agarose gels, and amplification was considered successful when one clear distinct band was visible in the expected size range. In total, 100% of the developed microsatellite markers we selected could be successfully amplified in two populations of M. rossii and four populations of O. rupifraga .…”
Section: Discussionmentioning
confidence: 99%
“…A total of 27 danshen plants were genotyped using 10 SSR molecular markers to analyze the genetic diversity existing between and within the seven S. miltiorrhiza cultivars ( Table S2 ). Danshen SSR genotyping analysis method used established by Dr. Qi ZC [ 56 , 57 ].…”
Section: Methodsmentioning
confidence: 99%
“…Different methods may be applied for genotyping in plants. Microsatellite (Martins et al, 2013a;Ru et al, 2017;Qi et al, 2017) and DNA barcodes (Cameron & Fu, 2006;Qi et al, 2013) have been used for genotyping Smilax species and have shown phylogenetic relationships between different Smilax species. Additionally, Sulistyaningsih et al (2018) used the DNA barcode rbcL for phylogenetic analysis of Smilax spp.…”
Section: Molecular Barcode Sequencesmentioning
confidence: 99%
“…Morphological and molecular barcode analysis are lacking for S. purhampuy in Ecuador, despite its medicinal use. Phylogenetic analysis of the Smilax genus includes microsatellites (Martins et al, 2013a;Ru et al, 2017;Qi et al, 2017) which are also informative tools for genetic diversity and gene flow studies. Other methods for the phylogenetic analysis of plants includes DNA barcodes, which may be used as a complementary tool in the taxonomic identification of the species; for instance, the plastid genome regions atpF-atpH spacer, matK gene, rbcL gene, rpoB gene, rpoC1 gene, psbK-psbI spacer, and trnH-psbA spacer have been tested as universal plant barcodes (CBOL Plant Working Group, 2009).…”
Section: Introductionmentioning
confidence: 99%